Dampak perceraian terhadap moral anak di desa koto dua kecamatan pesisir bukit kota sungai penuh - Kaffah, Fisalmi; Sutja, Akmal (Civic Education Perspective Journal, 2024)
This study aims to find out more deeply about the impact of divorce on children's morals in Koto Dua Village. This research method uses qualitative research with descriptive research type. The data collection techniques in this study are observation, interviews, and documentation. Based on the results of the study, it shows that the impact of parental divorce can cause children to have broken homes, so they seek pleasure outside the home, and go the wrong way, such as during school they violate the rules that apply at school, then also have an impact on the child's economy after their parents divorce, children's school is dropped out due to lack of living expenses, economic limitations and added to the lack of motivation for children to learn because there is no good support from both parents. The study can be concluded that the impact of divorce on children's morals is very large, children's morals who are not educated properly are caused by divorce factors so that there is a decline in morals among children.